2023
DOI: 10.1097/shk.0000000000002133
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes and Microvesicles From Adipose-Derived Mesenchymal Stem Cells Protects the Endothelial Glycocalyx From LPS Injury

Abstract: Introduction: Endothelial glycocalyx damage occurs in numerous pathological conditions and results in endotheliopathy. Extracellular vesicles, including exosomes and microvesicles, isolated from adipose-derived mesenchymal stem cells (ASCs) have therapeutic potential in multiple disease states; however, their role in preventing glycocalyx shedding has not been defined. We hypothesized that ASC-derived exosomes and microvesicles would protect the endothelial glycocalyx from damage by LPS injury in cultured endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…ADSC-Ex plays a crucial role in intercellular communication, as they can transfer bioactive molecules, such as proteins, lipids, and nucleic acids, to recipient cells [ 24 ]. In recent years, there has been a growing interest in the therapeutic potential of ADSC-Ex in various diseases, including tissue injury, inflammation, and cancer [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…ADSC-Ex plays a crucial role in intercellular communication, as they can transfer bioactive molecules, such as proteins, lipids, and nucleic acids, to recipient cells [ 24 ]. In recent years, there has been a growing interest in the therapeutic potential of ADSC-Ex in various diseases, including tissue injury, inflammation, and cancer [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Matric metalloproteinases play an important role in the degradation of the glycocalyx during injury. 18,24 The glycocalyx sheddases found to have been affected by DMSO in a hypoxia-reoxygenation injury include MMP24 and MMP25. 4 In the present study, an LPS injury was examined, as HUVECs were injured with LPS.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has shown that DMSO can prevent the membrane organization that leads to endothelial glycocalyx damage in hypoxia-reperfusion. Matric metalloproteinases play an important role in the degradation of the glycocalyx during injury 18,24 . The glycocalyx sheddases found to have been affected by DMSO in a hypoxia-reoxygenation injury include MMP24 and MMP25 4 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, the treated cells were stained for 1 h with FITC-WGA (2 μg/mL, 100 μL) to label vascular endothelial glycocalyx, washed twice with PBS, fixed with 4% paraformaldehyde for 15 min, washed twice with PBS, and analyzed under a fluorescence microscope. As a positive control, the cells were stimulated with lipopolysaccharide, which is known to degrade the vascular endothelial glycocalyx [ 40 ].…”
Section: Methodsmentioning
confidence: 99%